Middle region of the Borrelia burgdorferi surface‐located protein 1 (Lmp1) interacts with host chondroitin‐6‐sulfate and independently facilitates infection. (31st August 2015) - Yang, Xiuli; Lin, Yi‐Pin; Heselpoth, Ryan D.; Buyuktanir, Ozlem; Qin, Jinhong; Kung, Faith; Nelson, Daniel C.; Leong, John M.; Pal, Utpal
Summary: Borrelia burgdorferi surface‐located membrane protein 1, also known as Lmp1, has been shown to play critical roles in pathogen evasion of host‐acquired immune defences, thereby facilitating persistent infection. Lmp1 possesses three regions representing potentially discrete domains: Lmp1N, Lmp1M and Lmp1C. Because of its insignificant homology to known proteins, how Lmp1 or its specific regions contribute to microbial biology and infection remains enigmatic. Here, we show that distinct from Lmp1N and Lmp1C, Lmp1M is composed of at least 70% alpha helices and completely lacks recognizable beta sheets. The region binds to host glycosaminoglycan chondroitin‐6‐sulfate molecules and facilitates mammalian cell attachment, suggesting an adhesin function of Lmp1M. Phenotypic analysis of the Lmp1‐deficient mutant engineered to produce Lmp1M on the microbial surface suggests that Lmp1M can independently support B .  burgdorferi infectivity in murine hosts. Further exploration of functions of Lmp1 distinct regions will shed new light on the intriguing biology and infectivity of spirochetes and help develop novel interventions to combat Lyme disease.